From Cuisine to Connection: How Cultural Encounters and Surprise Gestures Enrich Restaurant Experiences For International Tourist Dating Couples In Maldives and Thailand - Herjanto, Halimin; Boone, Sara (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
Dating couples are considered promising by restaurant markets, as they are willing to spend a substantial amount on dining out. Yet, the extant literature has not fully investigated this segment. This study aims to examine this segment by exploring the restaurant satisfaction of international tourist dating couples (ITDCs) in Thailand and the Maldives. A total of 202 ITDC’s comments on the TripAdvisor site were coded and analyzed using NVIVO-14. The findings show that general and common restaurant attributes (i.e., the quality of food and service, a restaurant’s physical attributes, and price) are responsible for ITDCs’ dining out experience. Interestingly, the study reveals that new attributes such as cultural encounters, surprise gestures, and chef/manager encounters also play a substantial role in determining such experiences. The findings of this research contribute to customer experience and satisfaction literature by identifying key decision-making factors influencing ITDCs' restaurant choices while offering practical recommendations. For example, restaurants are encouraged to utilize local tableware (e.g., banana leaves) and assign local names to foster cultural connections, offer surprise gestures like customized thank-you cards and small gifts, and promote chef-customer interactions to describe dishes. To the authors’ knowledge, this is the first thematic analysis study on ITDCs, providing valuable insights into the core attributes shaping their restaurant experiences.